New frontiers in mining complex patterns : 4ht International Workshop, NFMCP 2015, held in conjunction with ECML-PKDD 2015, Porto, Portugal, September 7, 2015, Revised selected papers /: 4ht International Workshop, NFMCP 2015, held in conjunction with ECML-PKDD 2015, Porto, Portugal, September 7, 2015, Revised selected papers. (2016) - Unknown
No abstract available